2021
DOI: 10.1038/s41467-020-20768-y
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 nucleocapsid phosphoprotein forms mutually exclusive condensates with RNA and the membrane-associated M protein

Abstract: The multifunctional nucleocapsid (N) protein in SARS-CoV-2 binds the ~30 kb viral RNA genome to aid its packaging into the 80–90 nm membrane-enveloped virion. The N protein is composed of N-terminal RNA-binding and C-terminal dimerization domains that are flanked by three intrinsically disordered regions. Here we demonstrate that the N protein’s central disordered domain drives phase separation with RNA, and that phosphorylation of an adjacent serine/arginine rich region modulates the physical properties of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
389
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(435 citation statements)
references
References 111 publications
12
389
0
4
Order By: Relevance
“…Recently, bioinformatic analyses proposed that the N protein of SARS-CoV-2, which contains low complexity domains (LCD) and a high tendency to phase separate, is capable of forming or regulating RNA granules through interactions with host SG-RNAs and proteins ( Cascarina and Ross, 2020 ; Moosa and Banerjee, 2020 ). A series of different studies showed that the N protein does phase separate with RNA and other proteins such as hnRNPs, RNA polymerase, and membrane-associated M protein ( Perdikari et al, 2020 ; Savastano et al, 2020 ; Lu et al, 2021 ). Importantly, phase separation is driven by genomic RNA elements and regulated by phosphorylation of N protein and ATP ( Carlson et al, 2020 ; Iserman et al, 2020 ; Dang et al, 2021 ).…”
Section: Stress Granules As Therapeutic Targets In Rna Virus Infection Cancer and Neurodegenerationmentioning
confidence: 99%
“…Recently, bioinformatic analyses proposed that the N protein of SARS-CoV-2, which contains low complexity domains (LCD) and a high tendency to phase separate, is capable of forming or regulating RNA granules through interactions with host SG-RNAs and proteins ( Cascarina and Ross, 2020 ; Moosa and Banerjee, 2020 ). A series of different studies showed that the N protein does phase separate with RNA and other proteins such as hnRNPs, RNA polymerase, and membrane-associated M protein ( Perdikari et al, 2020 ; Savastano et al, 2020 ; Lu et al, 2021 ). Importantly, phase separation is driven by genomic RNA elements and regulated by phosphorylation of N protein and ATP ( Carlson et al, 2020 ; Iserman et al, 2020 ; Dang et al, 2021 ).…”
Section: Stress Granules As Therapeutic Targets In Rna Virus Infection Cancer and Neurodegenerationmentioning
confidence: 99%
“…The SG nucleating factor G3BP1 [ 15 , 16 ] and other SG components were identified in the SARS-CoV-2 N protein interactome [ 5 , 17 ], suggesting SARS-CoV-2 like SARS-CoV regulates SGs mainly through N protein. The SARS-CoV-2 N protein is able to form condensates with RNA in vitro [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], in the cytoplasm of cells [ 21 , 25 ] and partially co-localizes within arsenite-induced SGs [ 26 ]. Several studies have shown that N protein sequesters G3BP1 and disassembles SGs [ 22 , 26 , 27 , 28 ], likely as a means to suppress the host immune response to favor virus replication.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that N protein sequesters G3BP1 and disassembles SGs [ 22 , 26 , 27 , 28 ], likely as a means to suppress the host immune response to favor virus replication. Recent studies show that IDR1 and NTD regulate N protein condensates affecting nucleic acid annealing and potentially implicated in viral packaging and assembly [ 21 , 22 , 25 ]. The SR linker region is phosphorylated by SRPK [ 29 ], GSK-3 [ 30 ] and Cdk1-GSK3 [ 18 ], influencing N protein condensates [ 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…[14] observe 38 vRNPs per SARS-CoV-2 virion [14]. Approximately 12 copies of the N protein are located in one vRNP in SARS-CoV-2 [32,33]. Multiplying those two numbers results in 456 copies of the N protein.…”
Section: Correcting the Copy Number Of Structural Proteinsmentioning
confidence: 99%